Avaliação do papel do receptor imune inato dectina-1 e antígenos solúveis de neospora caninum no tratamento da malária cerebral murina - Silva, Murilo Vieira da (2017)
Malaria is a disease that affects millions of people around the world, and its cerebral form carries a significant percentage of individuals to death, mainly children. Currently on the market there are some drugs with proven effect for the treatment of this disease, especially drugs acting on parasite replication. However, search for effective measures to control malaria brain picture remains a challenge for many research groups. For possible new drugs development, the detailed understanding of the parasite-host relationship in this infectious process needs to be elucidated. Thus, understand the role of standard recognition receptors as well as molecules of the parasite itself need to be known. In this work we evaluated the role of the β-glucan receptor, Detin-1 in the immune response against Plasmodium berghei-ANKA. We observed that in the absence of this receptor, animals are more resistant to infection, presenting delayed death, attenuated clinical signs of cerebral malaria, and less parasitemia. These results converge to the hypothesis that P. berghei-ANKA interacts with Dectin-1 to modulate the immune response, in order to favor its replication, consequently inducing cerebral malaria. On the other hand, there are many reports of coinfections and treatments with antigens of different parasites as therapeutic measures against malaria. These protocols are based on the beneficial use of modulatory effects (activators or inhibitors) of parasitic origin molecules to control the disease. Here we use soluble antigen of N. caninum (NLA), an apicomplexan parasite, as those of Plasmodium genus, for treatment of cerebral malaria. It has been observed that NLA treatment rescues animals from characteristic early death of cerebral malaria. We associated this rescue to lower levels of IFNγ and increased levels of TNFα in animals treated with NLA. We concluded that both innate receptor Dectin-1 and proteins of soluble antigen of N. caninum are potential targets for the development of therapeutic measures against cerebral malaria.